PSEUDO-PLATONO DEFINICIJOS GRAIKŲ FILOSOFINĖS TRADICIJOS KONTEKSTE. - Garbačiauskas, Paulius (Problems / Problemos, 2016)
The article discusses a phenomenon of philosophical definitions, a common feature of almost all Greek philosophical schools, including the Pre-Socratics, and aims to cover the collection of Definitions, found in the Platonic corpus, and their place in the context of Greek philosophical tradition. This late interpolation is a dictionary of about 185 philosophically significant terms representing early Stoicism rather than Plato's Academy. Defining the terms was a common practice of philosophical thinking exercise, as is rather reliably endorsed by the ample number of surviving titles of various philosophical treatises, as well as stories of Greek comedy and anecdotic accounts recorded by Diogenes Laertius in Lives of Eminent Philosophers.